Characteristics Of Physical, Mechanical And Chemical Properties Of Cissus Sicyoides And Its Composites - M. irawan Apriandi; Nasmi Herlina Sari; Sinarep Sinarep (Protech Biosystems Journal, 2025)
This study aims to examine the characteristics of Cissus Sicyoides natural fibers extracted by two different methods, namely mechanical and boiling methods, and their application as reinforcing materials for epoxy resin-based composites. The characteristic of fibers was tested through physical and chemical properties, and fiber morphology, including tensile tests, FTIR, SEM and chemical composition. The results showed that the mechanical method produced fibers with higher tensile strength (431.41 MPa) and rougher surface structures, which support better mechanical bonding in the composite matrix. Meanwhile, the boiling method produced fibers with higher cellulose content (23.05%) and a cleaner and tidier surface. FTIR tests confirmed the presence of hydroxyl and carbonyl groups in both samples, while SEM results showed significant presence in the surface morphology and fiber cross-section. Composites made with fibers from the mechanical method had higher tensile strength (28.97 MPa) compared to composites from the boiling method (9.42 MPa). Overall, Cissus Sicyoides fiber has the potential as a composite reinforcing material with a mechanical extraction method that is superior in producing better mechanical performance. The findings of this study add to the use of local natural fibers as an alternative, ecologically friendly composite reinforcement for lightweight buildings.